Reconsidering esport: Economics and executive ownership - Karhulahti Matti (Akademia Wychowania Fizycznego Jozefa Pilsudskiego w Warszawie, 2025)
This article starts with a literary review of the conceptual frames through which esport has been labeled academically. It shows how the concept of “electronic” has been taken as the core term for labelling esport, often accompanied by a strong emphasis on “professionalism.” The literary review is followed by the submission of an alternative conceptual frame based on the economic notion of executive ownership, which provides a theoretical grounding for esport as a cultural phenomenon. In accordance with the above, the article concludes with a reframed look at the history of esport and suggests commercial analog gaming (especially Magic: The Gathering) as its point of origin.
Esports, economics, games, theory, history, politics